Issues and Challenges in the Practice of Performance Appraisal Activities in the 21st Century. - Rusli, Ahmad; Sopian, Bujang (Contemporary Research Center CRC Publicat, 2013)
In every organisation, employees play a vital role in determining its survival. Employees become the ultimate asset to ensure that the organisation operates as planned. The relation between the appraisal system and the organisation’s strategy is used as a strategic tool to achieve the organisation’s vision. This will evidently be a key factor in communicating values, promoting flexibility and maximizing individual potentials and contributions. Very often, employees who are not happy with the practice of the appraisal activities will send a huge impact on the organisation’s image. In the 21st century, performance appraisal activities continue to become one of the most important functions in human resource management. The work environment and the employees have become more in tune because of the massive usage of information and communication technology (ICT) in every organisation. This paper explains the relationship of the 21st century with performance appraisal activities and explores issues as well as challenges that arise in the appraisal activities.